2020
DOI: 10.1021/jasms.0c00063
|View full text |Cite
|
Sign up to set email alerts
|

Direct Analysis of Doping Agents in Raw Urine Using Hydrophobic Paper Spray Mass Spectrometry

Abstract: In this study, the direct analysis of doping agents in urine samples with no sample preparation by a modified paper spray mass spectrometry (PS-MS) methodology has been demonstrated for the first time. We have described a paper surface treatment with trichloromethylsilane using a gas-phase reaction to increase the ionization of target compounds. This approach was applied for the analysis of two classes of banned substances in urine samples: anabolic agents (trenbolone and clenbuterol) and diuretics (furosemide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 66 publications
0
39
0
Order By: Relevance
“…The study furthermore combined the analysis with field asymmetric ion mobility spectrometry (FAIMS) to further improve assay sensitivity and selectivity. Rossini et al took a similar approach, applying hydrophobic PSI to the detection of doping agents in raw urine 54 . In this study, the paper surface was treated with trichloromethylsilane to improve the ionization of target analytes, specifically the anabolic agents clenbuterol and trenbolone, and the diuretics furosemide and hydrochlorothiazide.…”
Section: Applications Of Ambient Ionization Mass Spectrometrymentioning
confidence: 99%
“…The study furthermore combined the analysis with field asymmetric ion mobility spectrometry (FAIMS) to further improve assay sensitivity and selectivity. Rossini et al took a similar approach, applying hydrophobic PSI to the detection of doping agents in raw urine 54 . In this study, the paper surface was treated with trichloromethylsilane to improve the ionization of target analytes, specifically the anabolic agents clenbuterol and trenbolone, and the diuretics furosemide and hydrochlorothiazide.…”
Section: Applications Of Ambient Ionization Mass Spectrometrymentioning
confidence: 99%
“…On the other hand, low-polarity analytes interact less with the cellulosic paper, which favors their elution while improving analyte ionization. Chemical modifications of the paper surface can help improve the efficiency of PSI and increase analyte-specific sensitivity (Damon et al, 2016;Filho et al, 2020;Rossini et al, 2020).…”
Section: Type Of Chemistrymentioning
confidence: 99%
“…While the masking properties of diuretics are today significantly more limited than 30 years ago, diuretics are still considered as potentially performance‐enhancing in selected sports 153 . In the light of comparably high MRPL of 200 ng/ml established for most diuretics 51 and the xenobiotic nature of the analytes, omitting chromatographic separation has been considered as viable option, and Rossini et al demonstrated the capability of paper spray MS with surface‐modified grade‐I filter paper to allow for the detection of furosemide and hydrochlorothiazide in spiked urine samples at low ng/ml concentrations 154 . A volume of 6 μl of urine was spotted onto a trichlorosilane‐derivatized paper triangle interfaced to a linear ion trap MS system, and target compounds were detected in MS/MS mode, offering an alternative analytical ITP approach for a subset of target compounds in doping controls if adequate reproducibility and robustness is proven.…”
Section: Diuretics Other Masking Agents and Stimulantsmentioning
confidence: 99%